1978
DOI: 10.1002/cne.901770206
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the half retinal projection to the tectum in goldfish: An electrophysiological and Anatomical study

Abstract: The topographical retino-tectal projection of goldfish was electrophysiologically mapped a t various intervals after surgical removal of the nasal half of the retina and pigment epithelium. The remaining projection was initially restricted to the appropriate rostral half of the tectum, even if the nerve was crushed and allowed to regenerate. But later, after 137 days or more, it showed a progressive expansion onto the foreign caudal half of the tectum. The magnification factor, the number of micrometers of tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 28 publications
7
95
1
Order By: Relevance
“…Thus, map expansions and contractions observed after retinal and tectal/collicular ablations (45)(46)(47)(48)(49), when competition between axons is modified, are consistent with the dual gradient, servomechanism, and competition models, because each includes competition as a mechanism to ensure uniform target coverage (4,21). Perhaps for this reason, recent reviews of mapping in the literature present the prevailing model for the topographic map formation as a dual gradient model along the A-P axis and a form of servomechanism along the M-L axis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, map expansions and contractions observed after retinal and tectal/collicular ablations (45)(46)(47)(48)(49), when competition between axons is modified, are consistent with the dual gradient, servomechanism, and competition models, because each includes competition as a mechanism to ensure uniform target coverage (4,21). Perhaps for this reason, recent reviews of mapping in the literature present the prevailing model for the topographic map formation as a dual gradient model along the A-P axis and a form of servomechanism along the M-L axis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism that is believed to regulate the number and efficacy of synaptic contacts is competition. The original idea, and much of the evidence for competitive interactions, come from studies of afferent projections in the visual system of vertebrates (Hubel et al, 1977;Schmidt et al, 1978;Tieman, 1984;Wiesel and Hubel, 1965). A direct demonstration, however, of the effects of competition on individual central synapses is difficult to obtain.…”
mentioning
confidence: 99%
“…When half of tectum is removed and the optic nerve crushed, fibers from the entire retina become squeezed into the remaining half tectum to form a compressed retinotopic projection from the entire retina (13,44). Similarly, when half of retina is removed and the nerve crushed, regenerating fibers from the remaining half of retina can expanded across the entire tectum (36). Since the general result is that all fibers become accommodated and all tectum becomes innervated, it has been suggested that fibers compete for tectal space (18,26,39,42).…”
Section: Number Of Fibers and Competitionmentioning
confidence: 99%
“…There are reasons to believe that the regulation of axonal growth is more complicated than a simple response to local cues. One reason for thinking this is the plasticity of the mapping (13,26,36,39,42,44). When half of tectum is removed, fibers will form a compressed retinotopic projection onto the remaining half of tectum.…”
Section: Introductionmentioning
confidence: 99%